Coatable cores for modified release formulations
Patent Information
- Application Number
- JP2023093381
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-12-07
- Filing Date
- 2023-06-06
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2039-12-05
Smart Images

Figure 0007635298000017 
Figure 0007635298000018 
Figure 0007635298000019
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for preparing a coatable core for oral formulations, preferably modified release formulations for oral administration, and a delayed release formulation prepared therefrom. In particular, it relates to a coatable core for delayed release formulations of drugs delivered to the intestine. The coatable core of the present invention can also be used in formulations for delivering drugs to the stomach or small intestine. [Background technology]
[0002] Intestinal targeting of drugs is well known and has been known for over 100 years. Generally, the drug is targeted to the small intestine, but the colon can be utilized as a means to achieve local or systemic therapy. Drug coating requirements vary depending on the target site. To reach the colon, the drug must pass through the small intestine, so it is a requirement that a delayed release coating intended to release the drug in the colon does not release the drug in the small intestine.
[0003] Coated products for release in the small intestine generally use polymer coatings that dissolve or disintegrate depending on the pH. In the low pH environment of the stomach, the polymer coating is insoluble. However, upon reaching the small intestine, the pH rises to 5 or higher and the polymer coating dissolves or disintegrates. Commonly used coatings are those that contain ionizable carboxyl groups. At high pH, the carboxyl groups ionize and cause the polymer coating to disintegrate or dissolve. Common polymers of this type used include Eudragit® L and Eudragit® S.
[0004] Various methods are known to improve the release in the small intestine by ensuring early release of the drug. US2008 / 0200482 is one of many references that discloses partially neutralizing carboxyl groups to lower the pH at which disintegration occurs. WO2008 / 135090 discloses tablets with an inner coating of partially neutralized material and an outer coating with reduced or no neutralization, which are said to disintegrate at an earlier time point when delivered from the stomach.
[0005] Drug release in the colon requires alternative means. The colon is susceptible to many pathologies, such as inflammatory bowel disease, irritable bowel syndrome, constipation, diarrhea, infections and carcinomas. In such conditions, drugs that target the colon will maximize the therapeutic effect of treatment. The colon can also be used as a portal for drugs to enter the systemic circulation. Various formulations, including prodrugs and formulated dosage forms, have been developed for colonic drug delivery, but the latter is more common because the proven concepts can be applied to other drugs.
[0006] The high density of bacterial populations in the colon has also been exploited in developing dosage forms for colonic drug delivery through the use of naturally occurring polysaccharides as digestible carrier materials that constitute the substrates for many enzymes produced by resident glycemic bacteria. These materials can pass intact through the upper gastrointestinal region but are digested once in the colon. Examples include starch, amylopectin, amylose, pectin, chitosan, galactomannan and guar gum.
[0007] One of the main attractions of using polysaccharides in this bacterial enzyme approach to colonic drug delivery is that the materials used are food grade and therefore safe for human use.They are usually applied as coatings or incorporated into core materials as matrix carriers, resulting in the release of loaded drug upon digestion by colonic bacterial enzymes upon entry into the colon.An example of such a formulation using amylose coating is disclosed in EP0343993A (BTG International Limited).
[0008] However, the main limitation with these naturally occurring materials is that they swell excessively in aqueous media, leading to leaching of the loaded drug in the upper gastrointestinal region. To circumvent this problem, naturally occurring materials have been used in mixtures with various impermeable materials.
[0009] EP0502032A (British Technology Group Ltd) teaches the use of an outer coating comprising a film-forming cellulosic or film-forming acrylate polymeric material and amorphous amylose for tablets comprising an active compound. The polymeric material used is a pH-independent release polymeric material.
[0010] An article in the Journal of Controlled Release (Milojevic et al;38;(1996);75-84) reports the results of an investigation into the incorporation of various insoluble polymers into amylose coatings to control the swelling of amylose. Various cellulosic and acrylate-based copolymers were evaluated, with commercially available ethylcellulose (Ethocel®) found to control swelling most effectively. Eudragit® L100, a pH-dependent soluble coating, is used, but only in a multi-layer system with an inner coating of amylose and a bioactive coating with an outer coating of Eudragit® L100.
[0011] Further amylose-based coating compositions are disclosed in WO 99 / 21536A (BTG International Limited). The coating composition comprises a mixture of amylose and a water-insoluble, pH-independent film-forming polymer formed from a water-insoluble cellulose or acrylate polymer material.
[0012] WO 99 / 25325 A (BTG International Limited) also discloses a delayed release coating comprising amylose and (preferably) ethylcellulose, or an insoluble acrylate polymer. The coating composition also includes a plasticizer, and the process finds particular application in the preparation of dosage forms comprising active substances that are unstable at temperatures above 60° C., since the composition is formed at temperatures below 60° C.
[0013] WO03 / 068196A (Alizyme Therapeutics Ltd) discloses a specific delayed release coating for bioactive prednisolone metasulfobenzoate sodium comprising glassy amylose, ethylcellulose and dibutyl sebacate.
[0014] The use of polysaccharides other than amorphous amylose in delayed release coatings is disclosed in GB2367002 (British Sugar PLC). Examples include guar gum, karaya gum, tragacanth gum and xanthan gum. Microparticles of these polysaccharides are dispersed in a water-insoluble film-forming polymer matrix formed, for example, from cellulose derivatives, acrylic polymers or lignin.
[0015] WO01 / 76562A (Tampereen Patenttitoimisto Oy) discloses an oral formulation containing a drug and chitosan (a polysaccharide obtained from chitin) to control its release. The drug and chitosan are mixed into a homogeneous mechanical powder mixture, granulated, and then optionally tableted. Granulation may be performed with an enteric polymer (e.g., a copolymer of methacrylic acid) or the granules may be provided with a porous enteric coating.
[0016] WO2004 / 052339A (Salvona LLC) discloses a pH-dependent drug release system that is a free-flowing powder of solid hydrophobic nanospheres comprising a drug encapsulated in pH-sensitive microspheres. The nanospheres are formed from the drug in combination with a wax material, and the pH-sensitive microspheres are formed from a pH-sensitive polymer (e.g., Eudragit® polymer) in combination with a water-sensitive material (e.g., a polysaccharide).
[0017] An article in the European Journal of Pharmaceutical Sciences (Akhgari et al;28;March 2006;307-314) reports the results of an investigation into the use of certain polymethacrylate polymers to control, inter alia, the swelling of inulin. The polymethacrylate polymers tested were Eudragit® RS; Eudragit® RL; a 1:1 mixture of Eudragit® RS and Eudragit® RL; Eudragit® FS; and a 1:1 mixture of Eudragit® RS and Eudragit® S.
[0018] US5422121 (Rohm GmbH) discloses an oral dosage form having a core containing at least one active ingredient encapsulated in a shell material comprising a polysaccharide mixed with a film-forming polymer and degrading in the colon. The weight ratio of polysaccharide to film-forming polymer is 1:2 to 5:1, preferably 1:1 to 4:1. Premature diffusion of the active ingredient from the core can be inhibited using a gastroresistant barrier layer. This reference illustrates inter alia a tablet having an inner barrier layer consisting of Eudragit® L30D and an outer layer comprising Eudragit® L30D and guar gum (Example 2).
[0019] WO 96 / 36321A discloses an oral dosage form comprising a core containing bisacodyl and an enteric polymer coating for the core, the coating comprising at least one inner coating and an outer coating, the inner coating or each of the inner coatings being an enteric polymer that begins to dissolve in aqueous media at a pH of about 5 to about 6.3, and the outer coating being an enteric polymer that begins to dissolve in aqueous media at a pH of about 6.8 to about 7.2. The inner enteric polymer coating material is selected from the group consisting of cellulose acetate phthalate, cellulose acetate trimellitate, hydroxypropyl methylcellulose phthalate, hydroxypropyl methylcellulose acetate succinate, polyvinyl acetate phthalate, poly(methacrylic acid, methyl methacrylate) 1:1, poly(methacrylic acid, ethyl acrylate) 1:1, and compatible mixtures thereof.
[0020] WO2013 / 164315A discloses a colonic drug delivery formulation comprising a core comprising a drug and a coating comprising an inner layer and an outer layer. A mixture of a pH-dependent film-forming polymeric material and a polysaccharide (e.g., starch) is used as the outer layer, and the inner layer is soluble in intestinal or gastrointestinal fluids. This reference illustrates, inter alia, a tablet core comprising 1200 mg of 5-aminosalicylic acid (5-ASA, also known as mesalamine or mesalazine) as an active compound. These tablet cores are prepared by wet granulation followed by fluid bed drying, blending and compression.
[0021] In a typical tablet compression process, a tableting or compression blend is introduced into a die and compressed into a tablet by two punches that fit into the top and bottom of the die. Compressing a tableting blend into a tablet generally requires the injection of a lubricant. The lubricant reduces friction between the particles or granules of the tableting blend in the filling unit and the surfaces of the punches and die during compression. The lubricant also reduces friction between the surfaces of the tablet core and the surfaces of the punches and die during ejection. The presence of a lubricant reduces the ejection force, reduces wear on the punches and die of the tablet press, and helps ensure that the tablet does not stick to the die and is ejected cleanly from the tablet press without cracking or breaking. Usually, a lubricant is added to the tableting blend itself just before compression. This is known as internal lubrication. The lubricant particles form a boundary layer on the particles or granules of the tableting blend. The presence of a lubricant in the tableting blend improves the flowability of the blend by reducing friction between the particles. The 1200 mg tablet core exemplified in WO2013 / 164315A contains 0.5 wt.% magnesium stearate as an internal lubricant. During pilot plant production of delayed release formulations as disclosed in WO2013 / 164315A, it has been identified that an amount of lubricant of 0.5 wt.% per tablet is insufficient for proper lubrication of the tablet press in certain circumstances, especially for tablet cores over 1200 mg. This is indicated by the ejection pressure exceeding the limit set on the tablet press.
[0022] However, increasing the amount of internal lubricant may result in an undesirable decrease in tablet hardness and an undesirable increase in tablet friability, in addition to the tendency for capping to occur. "Capping" is a term used to describe the partial or complete horizontal separation of the top or bottom of a tablet from the tablet body, like a cap. This usually occurs during tablet ejection from the tablet press, but can also occur in subsequent operations. High levels of internal lubricant can also lead to extended disintegration times of tablet cores and risk of reduced solubility due to the presence of hydrophobic boundary layers surrounding the particles of the tableting blend and the presence of hydrophobic bridges formed in the final compressed tablet. There is also the possibility of stability problems during storage due to incompatibility of certain active pharmaceutical ingredients (APIs) with hydrophobic lubricants. It is therefore desirable to provide an improved method for producing coatable cores with high drug loads. Coatable cores should have low friability and high hardness, and should be capable of fast disintegration times and fast drug release.
[0023] A further problem with existing delayed release formulations for delivery of drugs (e.g., 5-ASA) is that patients are often required to take multiple tablets to receive the required daily dose of the drug. Therefore, it is further desirable to provide a modified release formulation for oral administration having a coatable core with high dose strength and minimal overall size, as this can reduce dosing frequency and improve patient compliance. [Brief description of the drawings]
[0024] [Figure 1] FIG. 1 is a graph showing the correlation between compression pressure and tablet hardness for 1600 mg 5-ASA tablet cores produced using an external lubricant according to Examples 2A-2G. [Diagram 2]FIG. 2 is a graph showing the correlation between tablet hardness and friability for 1600 mg 5-ASA tablet cores produced using external lubricants according to Examples 2A-2G. [Diagram 3] FIG. 3 is a graph showing the correlation between compression pressure and tablet hardness for 1600 mg 5-ASA tablet cores produced using internal lubricants according to Comparative Examples 3A-3H. [Figure 4] FIG. 4 is a graph showing the correlation between tablet hardness and friability for 1600 mg 5-ASA tablet cores prepared using internal lubricants according to Comparative Examples 3A-3H. [Diagram 5] FIG. 5 is a graph comparing drug release as a function of time from coated 5-ASA tablets according to Examples 5 and 6 when pre-exposed to 0.1 M HCl for 2 hours followed by exposure to Krebs buffer (pH 7.4) for 10 hours. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] According to a first aspect of the present invention there is provided a method for producing a coatable core for a modified release formulation for oral administration comprising the steps of: the coatable core has a high drug loading of at least 70% by weight based on the total weight of the coatable core; The method comprises the steps of: granulating a composition comprising the drug and at least one binder to form granules; blending the granules with a pharma- ceutically acceptable disintegrant and optionally one or more additional pharma-ceutically acceptable excipients to form a compression blend, the disintegrant being present in an amount of from about 0.5% to about 5% by weight, based on the total weight of the coatable core; and compressing the compression blend using an external lubrication compression technique to form a coatable core. The method comprises:
[0026] The process of the present invention advantageously produces coatable cores with low friability, high hardness, fast disintegration time and fast drug release that was neither anticipated nor predicted in the art.
[0027] Granules can be formed using a wet granulation or a dry granulation process. In embodiments where the granules are formed using a wet granulation process, the composition comprising the drug and at least one binder further comprises a granulation liquid.
[0028] The granulation liquid may include, but is not limited to, water, organic solvents, water-alcohol mixtures (e.g., water / ethanol mixtures or water / isopropanol mixtures) or water-organics (e.g., water / acetone mixtures). Suitable organic solvents include, but are not limited to, ethanol, isopropyl alcohol, acetone, dichloromethane, and combinations thereof. Preferably, the granulation liquid is water.
[0029] The binder may be added as a solution along with the granulating liquid or may be part of the powder bed which is then granulated with the granulating liquid.
[0030] The binder can be any suitable binder known to those skilled in the art, for example, sugar or polymer.Preferred synthetic polymer binders include, but are not limited to, hydroxypropyl cellulose, hydroxypropyl methylcellulose (HPMC or hypromellose, e.g., Pharmacoat® 603), microcrystalline cellulose (e.g., Avicel® pH102), methylcellulose, ethylcellulose, polyvinylpyrrolidone (PVP), sodium carboxymethylcellulose, polyvinyl alcohol (PVA), polyethylene glycol 4000 (PEG 4000), and polyethylene glycol 6000 (PEG 6000).Preferred natural polymer binders include, but are not limited to, starch, modified starch, pregelatinized starch, acacia gum, guar gum, tragacanth gum, xanthum gum, gelatin, sucrose solution, and maltodextrin solution. The binder is preferably present in an amount of about 3% by weight or less, preferably about 2% by weight or less, more preferably about 1% by weight or less, and most preferably about 0.5% by weight or less, based on the total weight of the coatable core.
[0031] Granulation can be carried out using any suitable mixer or granulator known in the art. For example, wet granulation can be carried out using heavy-duty mixing equipment, such as a kneader or high shear mixer granulator. Examples of suitable machines include Hobart mixers, Sigma type kneaders, V-blenders with intensifier bars, Lodige mixer choppers, Diosna high shear mixers and GEA high shear mixers. Granulation can be carried out using fluidized bed dryers (e.g., Diosna fluidized bed dryers or GEA fluidized bed dryers). It is preferred to carry out granulation using a high shear mixer granulator. Granulation is usually carried out with an acceptable low level of residual solvent for a time sufficient to produce granules of the required bulk density.
[0032] In the embodiment where the granules are formed using a wet granulation process, the wet granules are dried and then blended.Preferably, the wet granules are dried so that the dried granules have a moisture content (Loss on Drying) in the range of less than about 0.6%, more preferably less than about 0.4%, more preferably less than about 0.3%, and most preferably less than about 0.2%. Loss on Drying (LOD) is measured according to the European Pharmacopoeia (Ph.Eur.2.2.32).Preferably, the granules are sieved before and / or after drying to break up large lumps or agglomerates.
[0033] The granules are mixed with a pharmacologic acceptable disintegrant and optionally one or more additional pharmacologic acceptable excipients to form a compression blend. Preferably, the excipients are preblended and then blended with the granules. Optional pharmacologic acceptable excipients include, but are not limited to, filler or diluent materials, such as lactose or cellulosic materials, such as microcrystalline cellulose (e.g., Vivapur® 102), and flow regulators, such as colloidal silicon dioxide (e.g., Aerosil® 200).
[0034] The disintegrant is present in an amount of about 0.5% by weight or more and about 5% by weight or less, based on the total weight of the coatable core.Preferably, the disintegrant is present in an amount of about 0.5% by weight or more and about 3% by weight or less, based on the total weight of the coatable core.The disintegrant can be any suitable disintegrant known by those skilled in the art, such as croscarmellose sodium (e.g., Ac-Di-Sol®, Nymcel® ZSX, Primellose®, Solutab® and Vivasol®), cross-linked polyvinylpyrrolidone (e.g., Kollidon® and Polyplasdone™), cross-linked alginic acid (e.g., alginic acid NF and Satialgine®), calcium silicate and sodium starch glycolate (e.g., Explotab® and Vivastar® P).A particularly preferred disintegrant is sodium starch glycolate.
[0035] The compression blend is compressed using a compression process with external lubrication. External lubrication refers to the application of lubricant to the tablet press (such as a tablet press). Lubricant can be applied to the dies and / or punches of the tablet press. Typically, lubricant is sprayed onto the dry dies and / or punches using an external lubrication system, such as the Matsui Exlub system or the PharmaSpray system from Pharma Technology. The exact operating parameters vary depending on the system used. Preferably, the lubricant is sprayed onto the dies and / or punches of the tablet press at a spray rate of about 300 g / h to about 500 g / h, more preferably 350 g / h to about 450 g / h, an atomizing air pressure of about 30 kPa to about 50 kPa, and a pressure of dust extraction of about 250 Pa to about 500 Pa. This system allows a consistent amount of lubricant to be applied to the tablets throughout the entire batch and between batches of tablets. Excess lubricant is removed using a vacuum system.
[0036] The compression blend itself may optionally comprise one or more pharmacologically acceptable lubricants, i.e., internal lubricants. The internal lubricants are preferably present in the compression blend in an amount of about 0.5% by weight or less, preferably about 0.25% by weight or less, more preferably about 0.1% by weight or less, and most preferably about 0.05% by weight or less, based on the total weight of the coatable core.
[0037] The external or internal lubricant can be any suitable lubricant known to those skilled in the art.Preferred lubricants include, but are not limited to, magnesium stearate, calcium stearate, stearic acid, hydrogenated vegetable oil (e.g., Sterotex®, Lubritab® and Cutina®), mineral oil, polyethylene glycol 4000-6000, sodium lauryl sulfate (SLS), glyceryl palmitostearate (e.g., Precirol®), glyceryl behenate (Compitrol® 888), sodium benzoate or sodium fumarate stearate.A particularly preferred lubricant is magnesium stearate.
[0038] Compression of the compression blend can be carried out using any suitable tablet press known in the art. An example of a suitable tablet press is a rotary tablet press (e.g., Fette P1200 tablet press). The exact operating parameters of the tablet press will vary depending on the machine used.
[0039] Preferably, the compression speed during the compression step is from about 1,000 tablets per hour to about 60,000 tablets per hour, preferably from about 10,000 tablets per hour to about 50,000 tablets per hour, more preferably from about 15,000 tablets per hour to about 40,000 tablets per hour, more preferably from about 25,000 tablets per hour to about 35,000 tablets per hour, for example about 30,000 tablets per hour. Compression speeds above about 30,000 tablets per hour usually have a negative effect on the quality of the cores.
[0040] The compression force depends on the compressibility of the compression blend and the desired physical properties of the tablet core. Typical compression forces for use in the method of the present invention range from about 25 to about 35 kN, for example, about 29 kN.
[0041] The granules preferably have a bulk density of at least about 450 g / L to about 750 g / L, preferably about 540 g / L to about 700 g / L. Bulk density was measured by weighing 100 g of dry granules into a graduated cylinder and recording the volume according to the European Pharmacopoeia (Ph.Eur.2.9.34).
[0042] The pressed blend preferably has a bulk density of at least about 500 g / L to about 800 g / L, preferably about 600 g / L to about 750 g / L.Preferably, the pressed blend has a moisture content (LOD) in the range of about 0.5% to about 1.4%, more preferably about 0.7% to about 1.0%, and most preferably about 0.7% to about 0.8%.
[0043] According to a second aspect of the present invention there is provided a coatable core for a modified release formulation for oral administration comprising: A high drug content of at least 70% by weight based on the total weight of the coatable core and comprising the following components: Amounts of drug greater than about 1200 mg; a physiologi- cally acceptable lubricant in an amount of less than about 0.5% by weight, based on the total weight of said coatable core; a pharmacy acceptable disintegrant in an amount of about 0.5% to about 5% by weight, based on the total weight of the coatable core; and Optionally, one or more additional pharma- ceutically acceptable excipients. The coatable core is provided comprising:
[0044] According to a third aspect of the present invention there is provided a delayed release formulation for oral administration for delivering a drug to the intestine of a subject, comprising: The delayed release formulation comprises a core and a coating for the core, The core has a high drug load of at least 70% by weight, based on the total weight of the coatable core, and comprises the following components: Amounts of drug greater than about 1200 mg; a physiologi- cally acceptable lubricant in an amount of less than about 0.5% by weight, based on the total weight of said coatable core; a pharmacy acceptable disintegrant in an amount of about 0.5% to about 5% by weight, based on the total weight of the coatable core; and Optionally, one or more additional pharma- ceutically acceptable excipients. comprising the coating comprises an outer layer and, optionally, at least one layer located between the core and the outer layer selected from the group consisting of an isolation layer and an inner layer; the outer layer comprises a film-forming enteric polymer having a pH threshold of about pH 5 or higher, and optionally an enzymatically degradable polymer that is degraded by bacterial enzymes in the colon; the inner layer comprises a polymeric material that is soluble in intestinal or gastrointestinal fluids; the polymeric material is selected from the group consisting of at least partially neutralized polycarboxylic acid polymers and non-ionic polymers, with the proviso that when the polymeric material is a non-ionic polymer, the inner layer comprises at least one additive selected from a buffer and a base; The delayed release formulation is provided wherein the barrier layer comprises a non-ionic polymer that is soluble in intestinal or gastrointestinal fluids.
[0045] According to a fourth aspect of the present invention, there is provided a method for producing a delayed release formulation for oral administration for delivery of a drug to the colon according to the first aspect, said method comprising the steps of: forming a core comprising drug according to the method of the first aspect of the invention; coating said core with at least one coating preparation selected from the group consisting of a barrier layer coating preparation and an inner layer coating preparation to form an intermediately coated core, said barrier layer coating preparation comprising a non-ionic polymer that is soluble in intestinal or gastrointestinal fluids in a solvent system, and said inner layer coating preparation comprising a polymeric material that is soluble in intestinal or gastrointestinal fluids in a solvent system; coating the intermediate coated core with an outer coating formulation to form an outer coated core, the outer coating formulation comprising a film-forming enteric polymer having a pH threshold of about pH 5 or higher and optionally an enzymatically degradable polymer that is degraded by colonic bacterial enzymes in a solvent system. comprising The method is provided wherein the polymeric material that is soluble in intestinal or gastrointestinal fluids is selected from the group consisting of at least partially neutralized polycarboxylic acid polymers and non-ionic polymers, with the proviso that when the polymeric material is a non-ionic polymer, the inner layer comprises at least one additive selected from a buffer and a base.
[0046] The core can be directly coated using either the barrier layer coating formulation or the inner layer coating formulation to form the intermediate coated core, or the core can be directly coated using the barrier layer coating formulation to form a barrier layer coated core and then directly coated using the inner layer coating formulation to form the intermediate coated core.
[0047] In other embodiments having both a barrier layer and an inner layer where the third polymeric material of the inner layer is a non-ionic polymer, different non-ionic polymers can be used, however, in these embodiments it may be preferred that the same non-ionic polymer is used for the third polymeric material as the barrier layer non-ionic polymer.
[0048] The solvent system of the inner layer coating formulation is preferably aqueous based.
[0049] In embodiments in which the outer coating preparation comprises both a film-forming enteric polymer and an enzymatically degradable polymer, the outer coating preparation is preferably formed by combining the enzymatically degradable polymer in an aqueous medium (or solvent) with the film-forming enteric polymer in an organic medium (or solvent).
[0050] The organic medium may be selected from the group consisting of C1-C4 alcohols, methyl glycol, butyl glycol, acetone, methyl glycol acetate, and mixtures thereof. However, the organic medium preferably comprises ethanol. In a preferred embodiment, the organic medium is 85% to 98% ethanol, for example, about 96% ethanol.
[0051] The organic medium may contain from about 2% to about 10% polymer solids, for example about 6%.
[0052] The aqueous medium may be selected from the group consisting of water, a C1-C6 alcohol and mixtures thereof. However, the aqueous medium is preferably a mixture of water and a C1-C6 alcohol, preferably butan-1-ol. The ratio of water to alcohol in such a mixture is at least 5:1, preferably about 11:1.
[0053] Release from formulations according to the invention is typically delayed until at least the terminal ileum, and preferably the colon. Release from certain formulations may be sustained. However, in preferred formulations, release is pulsatile.
[0054] The time from the first exposure to conditions suitable for drug release to the onset of drug release is known as the "lag time". The lag time depends on various factors, such as the thickness and composition of the coating, and can vary from patient to patient. The formulations according to the invention usually exhibit a lag time of at least 10 minutes in colonic conditions. In most embodiments, the lag time is from about 10 minutes to about 8 hours. In certain cases, complete release of the drug can be achieved within 5 hours, e.g., within 4 hours, after exposure to these conditions.
[0055] A formulation is usually defined as gastroresistant if the drug release in acidic medium is less than 10% by weight after 2 hours. The formulation according to the present invention usually shows a drug release in acidic medium that is much less than 10% by weight and can be considered as gastroresistant. The formulation usually shows a drug release of less than 1% by weight in acidic medium, and usually shows virtually no drug release in acidic medium. When starch is combined with an acrylate film-forming material to form the outer layer of the coating of the core, a drug release of less than 5% occurs in 5 hours in simulated conditions of the stomach and small intestine.
[0056] Coatable Cores A coatable core ("core") is a solid formed by compression to which a coating can be applied. In a preferred embodiment, the coatable core is a tablet.
[0057] The core may be uncoated or may be pre-coated with a barrier layer and / or an inner layer onto which the outer coating is directly formed. The barrier layer and inner layer are described in more detail below.
[0058] The core comprises at least one drug. The core according to the embodiment of the present invention is designed to be used in a formulation for administering a wide range of drugs. The core usually comprises a single drug as the only therapeutically active ingredient. However, two or more drugs can be administered in a single coatable core.
[0059] Suitable drugs include those known for enteral administration using known delayed release oral formulations.The present invention can be used to administer drugs that have a local or systemic effect.
[0060] The identity of the drug in the core will obviously depend on the condition being treated. In this regard, the formulation has particular application in the treatment of IBD (including Crohn's disease and ulcerative colitis), IBS, constipation, diarrhea, infections and carcinomas (particularly colon or colorectal cancer).
[0061] The present invention is particularly applicable in the enteral administration of drugs that contain at least one acidic group (e.g., a carboxylic acid group). Such drugs can be acidic drugs or zwitterionic drugs. An example of such a drug is 5-aminosalicylic acid ("5-ASA" or mesalazine).
[0062] For the treatment or prevention of IBD, the core may comprise at least one drug selected from the group consisting of anti-inflammatory agents (e.g., 5-ASA), steroids (e.g., prednisolone, budesonide or fluticasone), immunosuppressants (e.g., azathioprine, cyclosporine, and methotrexate), antibiotics, and biologics (e.g., peptides, proteins, and antibody fragments). Suitable examples of biologics include alkaline phosphatase and anti-TNF antibodies (e.g., infliximab, adalimumab, certolizumab pegol, golimumab, and ustekinumab).
[0063] For the treatment or prevention of cancer, the core can comprise at least one antitumor agent.Suitable antitumor agents include fluorouracil, methotrexate, dactinomycin, bleomycin, etoposide, taxol, vincristine, doxorubicin, cisplatin, daunorubicin, VP-16, raltitrexed, oxaliplatin and its pharmacologically acceptable derivatives and salts.For the prevention of colon or colorectal cancer, mainly in patients suffering from colitis, the formulation can comprise anti-inflammatory agents 5-ASA, sulindac, celecoxib and / or eflornithine (DFMO).
[0064] For the treatment or prevention of IBS, constipation, diarrhea or infections, the core may comprise at least one active ingredient suitable for the treatment or prevention of these conditions.
[0065] Pharmacologically acceptable derivatives and / or salts of drugs may also be used in the coatable core. An example of a suitable salt of prednisolone is methylprednisolone sodium succinate. Another example is fluticasone propionate.
[0066] The present invention is particularly applicable in the treatment of IBD (especially ulcerative colitis) or in the prevention of colon or colorectal cancer (mainly in colitis patients), both using 5-ASA.It is also applied as a gateway for drugs to enter the systemic circulation via the colon.This is particularly advantageous for peptide and protein drugs that are unstable in the upper gastrointestinal tract.The present invention can also be utilized for the purpose of chronotherapy.
[0067] The core has a high drug content of at least about 70% by weight, based on the total weight of the coatable core. Preferably, the core has a drug content of from about 75% to about 95% by weight, or from about 80% to about 95% by weight, for example from about 85% to about 90% by weight.
[0068] The method according to the first aspect of the present invention can be used to produce cores of any size, for example, the drug can be present in the core in an amount of about 350 mg to about 1650 mg, or about 450 mg to about 1650 mg, or about 750 mg to about 1650 mg, or about 1150 mg to about 1650 mg, or about 1450 mg to about 1650 mg, or about 1550 mg to about 1650 mg. Preferably, the drug is present in a core amount selected from about 400 mg, about 800 mg, about 1200 mg, about 1500 mg or about 1600 mg. There is a particular advantage when the method of the first aspect of the present invention is used to produce a core comprising more than about 1200 mg of drug.
[0069] In embodiments of the second and third aspects of the invention, the drug is present in the core in an amount greater than about 1200 mg. Preferably, the drug is present in the core in an amount of from about 1250 mg to about 1650 mg, or from about 1450 mg to about 1650 mg, or from about 1550 mg to about 1650 mg, or about 1600 mg.
[0070] The core further comprises a disintegrant in an amount of about 0.5% by weight or more and about 5% by weight or less, based on the total weight of the coatable core. Preferably, the disintegrant is present in an amount of about 0.5% by weight or more and about 3% by weight or less, based on the total weight of the coatable core. The disintegrant can be any suitable disintegrant known by those skilled in the art, such as croscarmellose sodium (e.g., Ac-Di-Sol®) and sodium starch glycolate (e.g., Explotab® and Vivastar® P). A particularly preferred disintegrant is sodium starch glycolate.
[0071] In embodiments of the second and third aspects of the present invention, the core further comprises a pharma- ceutically acceptable lubricant in an amount of less than about 0.5% by weight, based on the total weight of the coatable core.Preferably, the lubricant is present in an amount of about 0.25% by weight or less, more preferably about 0.1% by weight or less, and most preferably about 0.05% by weight or less, based on the total weight of the coatable core.Preferred lubricants are as described above.
[0072] The core may further comprise one or more additional pharmacologically acceptable excipients, as detailed above.In this regard, the core is usually composed of a mixture of drug and a filler or diluent material, such as lactose or cellulose material (microcrystalline cellulose); a binder, such as hydroxypropylmethylcellulose (HPMC) or microcrystalline cellulose; a disintegrant, such as croscarmellose sodium or sodium starch glycolate; a flow regulator, such as colloidal silicon dioxide; and / or a lubricant, such as magnesium stearate.
[0073] The core preferably has a friability of 0% to less than about 0.5%, preferably 0% to less than about 0.25%, more preferably 0% to less than about 0.2%, and most preferably 0% to less than about 0.1%. Friability is defined as the tendency of a tablet or tablet core to chip, crumble, or split after compression. Friability is measured according to the European Pharmacopoeia (Ph.Eur.2.9.7) using a friability testing apparatus.
[0074] The core has a disintegration time in water of less than about 10 minutes, preferably less than about 5 minutes, measured according to the European Pharmacopoeia (Ph.Eur.2.9.1).
[0075] Preferably, the core has a hardness in the range of from about 200 N to about 330 N, more preferably from about 230 N to about 300 N, and most preferably from about 250 N to about 280 N. Tablet core hardness is measured using a tablet hardness tester according to the European Pharmacopoeia (Ph.Eur.2.9.1).
[0076] The core preferably has a height (thickness) of about 8.5 mm or more and about 9.2 mm or less. The thickness of the core (tablet) is usually measured using an electronic caliper.
[0077] Enzymatically degradable polymer (first polymer material) The enzymatically degradable polymer is degraded by one or more bacterial enzymes found in the colon of the subject (colonic bacterial enzymes). Such enzymes are produced by colonic bacteria and include amylases, such as α-amylase, β-amylase and iso-amylase; amylopullusinase, glucoamylase, α-glucosidase, maltogenic-amylase, glycosyltransferase and amylomaltase.
[0078] Those skilled in the art can use techniques that are part of their common general knowledge to determine whether a material is susceptible to degradation by bacteria in the colon, for example, a given amount of a given material can be exposed to an assay that includes enzymes from bacteria found in the colon, and the change in weight of the material over time can be measured.
[0079] The enzymatically degradable polymer is preferably a polysaccharide. Suitable polysaccharides include, but are not limited to, starch, amylose, amylopectin, chitosan, chondroitin sulfate, cyclodextrin, dextran, pullulan, carrageenan, scleroglucan, chitin, curdlan, levan and hemicellulose (e.g., xylan, glucuronoxylan, arabinoxylan, glucomannan, xyloglucan). The polysaccharide is preferably starch. Starch is usually extracted from natural products, such as cereals, legumes and tubers. Starch suitable for use in the present invention is usually food grade starch, including rice starch, wheat starch, corn (or maize) starch, pea starch, potato starch, sweet potato starch, tapioca starch, sorghum starch, sago starch and arrowroot starch. The use of corn starch is exemplified below.
[0080] Starch is usually a mixture of two different polysaccharides, amylose and amylopectin. Different starches can have different ratios of these two polysaccharides. Most native (unmodified) maize starches have from about 20% to about 30% by weight amylose, with the remainder being at least substantially composed of amylopectin.
[0081] Suitable starches include "high amylose" and "low amylose" starches. High amylose starches are particularly preferred.
[0082] A "high amylose" starch is a starch having at least 50% by weight amylose. Particularly suitable starches have from about 50% to about 75% by weight amylose, preferably from about 50% to about 70% by weight, more preferably from about 50% to about 65% by weight, and most preferably from about 50% to about 60% by weight, e.g., about 55% by weight amylose.
[0083] A "low amylose" starch is a starch having less than 50% by weight amylose and at least 50% by weight amylopectin, such as up to 75% by weight amylopectin, or even up to 99% by weight amylopectin.
[0084] Starches suitable for use in the present invention usually have at least 0.1% by weight amylose, for example at least 10% or 15% by weight, preferably at least 35% by weight. Such starches have up to 99.9% by weight amylopectin, for example up to 90% or 85% by weight, preferably up to 65% by weight. Such starches may have up to about 99% by weight amylose and 1% by weight or more amylopectin.
[0085] Starches suitable for use in the present invention may have up to 100% amylopectin, more typically from about 0.1% to about 99.9% by weight amylopectin. The starch may be, for example, unmodified waxy corn starch, which typically comprises about 100% amylopectin.
[0086] Preferred starches have up to 50% amylopectin by weight. Particularly suitable starches have from about 25% to about 35% amylopectin by weight, for example about 30% amylopectin by weight.
[0087] A person skilled in the art can determine the relative proportions of amylose and amylopectin in any given starch. For example, near infrared (NIR) spectroscopy can be used to determine the amylose and amylopectin content of starch using a calibration curve obtained by NIR using a mixture of known amounts of these two components produced in the laboratory. Furthermore, starch can be hydrolyzed to glucose using amyloglucosidase. A series of phosphorylation and oxidation reactions catalyzed by the enzyme results in the formation of reduced nicotinamide adenine dinucleotide phosphate (NADPH). The amount of NADPH formed is a constant ratio of the original glucose content. Test kits suitable for this procedure are available (e.g., R-Biopharm GmbH, Germany). Another method that can be used involves subjecting the coating to digestion with a bacterial enzyme, e.g., α-amylase, to produce short chain fatty acids (SCFAs) that can be quantified by gas-liquid chromatography using a capillary column.
[0088] Preferred starches are "commercial" starches, i.e., starches that do not require treatment before use in the context of the present invention. Examples of particularly suitable "high amylose" starches include Eurylon® 6 and Amylo N-400 starches (Roquette, Lestrem, France) or Amylogel 03003 (Cargill, Minneapolis, USA), all of which are maize starches having from about 50% to about 70% by weight amylose.
[0089] In a preferred embodiment, a mixture of two suitable polymers in suitable ratios is applied as a film coating to the core, and it has been found that it can at least minimize and substantially eliminate drug release in the stomach and small intestine. Subsequent drug release in the colon is believed to occur through a combination of active physiological triggers, namely dissolution of the second material, particularly Eudragit®, and digestion of the first material, e.g., starch or amylose.
[0090] Film-forming enteric polymer (second polymeric material) The film-forming enteric polymer is pH sensitive and has a pH threshold of about pH 5 or higher. The "pH threshold" is the pH below which it is insoluble and above which it is soluble. Thus, the pH of the surrounding medium causes the polymeric material to dissolve. Thus, no (or substantially no) enteric polymer dissolves below the pH threshold. When the pH of the surrounding medium reaches (or exceeds) the pH threshold, the second material becomes soluble.
[0091] "Insoluble" means that 1 g of the second material requires more than 10,000 mL of solvent (surrounding medium) to dissolve at a given pH.
[0092] By "soluble" it is meant that 1 g of the second material requires less than 10,000 mL, preferably less than 5000 mL, more preferably less than 1000 mL, and even more preferably less than 100 mL or less than 10 mL of solvent to dissolve at a given pH.
[0093] "Surrounding medium" preferably means the medium in the gastrointestinal tract, such as gastric or intestinal fluids. Alternatively, the surrounding medium may be an in vitro equivalent of the medium in the gastrointestinal tract.
[0094] The normal pH of gastric juice is usually in the range of 1 to 3. Enteric polymers are usually insoluble in gastric juice because they are insoluble below pH 5 and soluble above about pH 5. Such materials are sometimes called gastroresistant materials.
[0095] The enteric polymer has a pH threshold of at least pH 5, e.g., at least about pH 5.5, preferably at least about pH 6, more preferably at least about pH 6. The enteric polymer typically has a pH threshold of at most about pH 8, e.g., at most about pH 7.5, preferably at most about pH 7.2. Preferably, the second polymeric material has a pH threshold within the pH range found in intestinal fluids.
[0096] The pH of intestinal fluids may vary from person to person, but in healthy individuals is generally about pH 5-6 in the duodenum, about 6-8 in the jejunum, about 7-8 in the ileum, and about 6-8 in the colon. The second polymeric material preferably has a pH threshold of about 6.5 (i.e., insoluble at pH below 6.5 and soluble at pH above about 6.5), and more preferably has a pH threshold of about 7 (i.e., insoluble at pH below 7 and soluble at pH above about 7).
[0097] The pH threshold at which a material becomes soluble can be determined by simple titration techniques that are part of the common general knowledge of one of ordinary skill in the art.
[0098] Examples of suitable film-forming enteric polymers include acrylate polymers, cellulose polymers or polyvinyl polymers. Examples of suitable cellulose polymers include cellulose acetate phthalate (CAP), cellulose acetate trimellitate (CAT), hydroxypropyl methylcellulose phthalate (HPMCP) and hydropropyl methylcellulose acetate succinate. Examples of suitable polyvinyl polymers include polyvinyl acetate phthalate (PVAP).
[0099] The film-forming enteric polymer is preferably (meth)acrylic acid or (meth)acrylic acid C 1-4Copolymers of alkyl esters, for example, copolymers of methacrylic acid and methyl methacrylate. Such polymers are known as poly(methacrylic acid / methyl methacrylate) copolymers. Suitable examples of such copolymers include polymethacrylates, which are typically anionic and not sustained-release. The ratio of carboxylic acid groups to methyl ester groups in these copolymers ("acid:ester ratio") determines the pH at which the copolymer is soluble. The acid:ester ratio can be about 2:1 to about 1:3, for example about 1:1, or preferably about 1:2. The molecular weight (MW) of preferred anionic copolymers is typically about 120,000 to about 150,000, preferably about 135,000.
[0100] Preferred anionic poly(methacrylic acid / methyl methacrylate) copolymers include Eudragit® L (acid:ester ratio about 1:1; MW about 135,000; pH threshold about 6), Eudragit® S (acid:ester ratio about 1:2; MW about 135,000; pH threshold about 7) and Eudragit® FS (poly(methyl acrylate / methyl methacrylate / methacrylic acid); acid:ester ratio about 1:10; MW about 220,000; pH threshold about 7).
[0101] The film-forming enteric polymer can be a copolymer of methacrylic acid and ethyl acrylate, for example Eudragit® L100-55 poly(methacrylic acid / ethyl acrylate); acid:ester ratio about 1:1; MW about 250,000; pH threshold about 6. Eudragit® copolymers are manufactured and / or sold by Evonik (Darmstadt, Germany).
[0102] Mixtures of film-forming enteric polymers can be used if desired. Examples of suitable mixtures include mixtures of Eudragit® L and Eudragit® S, for example a 1:1 mixture. However, the use of certain film-forming polymeric materials alone, for example poly(methacrylic acid / methyl methacrylate) copolymers, is preferred.
[0103] The use of Eudragit® S alone as the film-forming enteric polymer is particularly preferred.
[0104] outer layer The ratio of the enzymatically degradable polymer to the film-forming enteric polymer is typically at least 1:99, such as at least 10:90, preferably at least 25:75. The ratio is usually 99:1 or less, such as 75:25 or less, preferably 60:40 or less. In some embodiments, the ratio may be 35:65 or less. In some preferred embodiments, the ratio is 10:90 to 75:25, such as 10:90 to 60:40, preferably 25:75 to 60:40. In some particularly preferred embodiments, the ratio is 15:85 to 35:65, such as 25:75 to 35:65, preferably about 30:70. In other particularly preferred embodiments, the ratio is 40:60 to about 60:40, such as about 50:50.
[0105] Optionally, conventional excipients, such as plasticizers selected from film-forming plasticizers (e.g., triethyl citrate), anti-adherents (e.g., glyceryl monostearate or GMS) and surfactants (e.g., polysorbate 80), may be included in an amount up to 30% by weight of the final composition of the outer coating preparation.
[0106] The thickness of the outer coating of the core is usually about 10 μm to about 150 μm. However, the specific coating thickness depends on the composition of the coating and the size of the core. For example, the coating thickness is directly proportional to the amount of polysaccharide in the coating. Thus, in an embodiment where the coating comprises high amylose starch and Eudragit® S in a ratio between about 30:70 and 60:40, the coating thickness can be about 70 μm to about 130 μm, preferably about 90 μm to about 110 μm.
[0107] The amount of enteric polymer in the outer coating is not related to the size of the core. The outer coating typically has a mass of about 2 mg / cm based on the dry weight of the enteric polymer. 2 More than about 10mg / cm 2 For example, about 2 mg / cm 2 More than 8mg / cm 2 Less than or equal to 3 mg / cm 2 More than 8mg / cm 2 Less than or equal to 4 mg / cm 2 More than 8mg / cm 2 Less than or equal to 6 mg / cm 2 More than 8mg / cm 2 Less than or equal to 7 mg / cm 2 More than 8mg / cm 2 For example, about 7.5 mg / cm 2 The typical core diameter is about 5×10 -4 m or more and less than about 25 mm.
[0108] Inner layer The formulation according to the invention optionally comprises an inner layer between the core and the outer layer, the inner layer comprising a third polymeric material that is soluble in intestinal or gastrointestinal fluids (both gastric and intestinal fluids).
[0109] By "gastric juice" we mean the aqueous fluid in the stomach of mammals, particularly humans. This fluid contains up to about 0.1N hydrochloric acid and significant amounts of potassium and sodium chloride, which play an important role in digestion by activating digestive enzymes and denaturing ingested proteins. Gastric acid is produced by cells lining the stomach, while other cells produce bicarbonate, which acts as a buffer to prevent the gastric juice from becoming too acidic.
[0110] By "intestinal fluid" we mean the fluid within the lumen of the intestine of a mammal, particularly a human. Intestinal fluid is a pale yellow, aqueous fluid secreted by glands lining the intestinal wall. Intestinal fluid includes fluids found in the small intestine, i.e., fluids found in the duodenum (or "duodenal fluid"), fluids found in the jejunum (or "jejunal fluid") and fluids found in the ileum (or "ileal fluid"), as well as fluids found in the large intestine, e.g., "colonic fluid".
[0111] Those skilled in the art can easily determine whether a polymer is soluble in gastric and / or intestinal fluids. If a polymer is soluble in water (or an aqueous solution, such as a buffer) at a pH of 1-3, the polymer is usually soluble in gastric fluid. Similarly, if a polymer is soluble in water (or an aqueous solution, such as a buffer) at a pH of 5-8, the polymer is usually soluble in intestinal fluids. Alternatively, the composition of gastric and intestinal fluids is known and can be reproduced in vitro. If a polymer is soluble in artificial gastric or intestinal fluids in vitro, it is usually soluble in gastric or intestinal fluids, respectively, in vivo.
[0112] In principle, any water-soluble film-forming polymer that is pharmacologically acceptable is suitable for use as the third polymeric material. The solubility of the water-soluble polymer may be pH-dependent. That is, the polymeric material may be a pH-sensitive polymer that has a pH threshold.
[0113] The polymeric material may be soluble in at least one fluid selected from gastric, duodenal, jejunal and ileal fluids. However, in a preferred embodiment, the solubility of the third polymeric material in water is pH independent, at least within the pH range found in the intestine. In a preferred embodiment, the third polymeric material is soluble in fluids in the stomach and anywhere in the intestine, i.e., gastrointestinal fluids.
[0114] The polymer suitable for use as the third polymeric material preferably comprises a group that can ionize to form an anion in aqueous medium. Such polymers are known in the art as "anionic" polymers. Suitable anionic polymers include polycarboxylic acid polymers, i.e., polymers or copolymers that comprise multiple carboxylic acid functional groups that ionize to form carboxylate anions in aqueous medium, such as intestinal fluid.
[0115] In embodiments in which the third polymeric material is a polycarboxylic acid polymer, it is preferred that the third polymeric material is at least partially neutralized (i.e., at least a portion of the carboxylic acid groups, e.g., at least 10%, preferably at least 25%, more preferably at least 50%, and most preferably at least 90%, are in the form of carboxylate anions). In particularly preferred embodiments, all of the carboxylic acid groups in the third polymeric material are in the form of carboxylate anions. Such polymers are referred to herein as "fully neutralized."
[0116] In a preferred embodiment, the second and third polymeric materials are based on the same polycarboxylic acid polymer, and the third polymeric material has a higher degree of neutralization than the second polymeric material. For example, for a particular polycarboxylic acid polymer, the second polymeric material can be in a non-neutralized form, and the third polymeric material can be in a partially or fully neutralized form. Alternatively, the second polymeric material can be in a partially neutralized form, and the third polymeric material can also be in a partially neutralized form (albeit in a more highly partially neutralized form) or fully neutralized form.
[0117] Examples of suitable polycarboxylic acid polymers include cellulose acetate phthalate (CAP), polyvinyl acetate phthalate (PVAP), hydroxypropyl methylcellulose phthalate (HPMCP), hydroxypropyl methylcellulose acetate succinate (HPMC-AS), cellulose acetate trimellitate (CAT), xanthan gum, alginates and shellac. However, the polycarboxylic acid polymer is preferably a polymer of (meth)acrylic acid and an alkyl (meth)acrylate (e.g., C 1-4 The anionic copolymers are typically selected from copolymers of methyl ester, alkyl, ester, methacrylic acid, and methacrylic acid. Particularly suitable are copolymers of methacrylic acid and methyl ester of methacrylic acid. Such polymers are known as poly(methacrylic acid / methyl methacrylate) copolymers or "polymethacrylates." The ratio of carboxylic acid groups to methyl ester groups in these copolymers ("acid:ester ratio") determines the pH at which the copolymer is soluble. The acid:ester ratio can be from about 2:1 to about 1:3, for example about 1:1, or preferably about 1:2. The molecular weight ("MW") of preferred anionic copolymers is typically greater than or equal to about 120,000 and less than or equal to about 150,000, preferably about 125,000 or about 135,000.
[0118] Preferred copolymers for the third polymeric material are described in detail in the section above relating to the second polymeric material and include Eudragit® L, Eudragit® S, Eudragit® FS30D, Eudragit® L30D-55 and Eudragit® L100-55.
[0119] Preferably, the exemplary polymers are used such that the third polymeric material is in at least a partially, and more preferably a fully, neutralized form.
[0120] Partially neutralized polymers suitable for use as the third polymeric material and their preparation methods are known in the art, for example from US2008 / 0200482A and W02008 / 135090A. These polymers can be fully neutralized by further adding base to the coating solution.
[0121] In a preferred embodiment, the third polymeric material is (meth)acrylic acid and (meth)acrylic acid C 1-4 It is an at least partially, preferably fully, neutralized copolymer of alkyl esters. In a particularly preferred embodiment, the third polymeric material is a fully neutralized copolymer of (meth)acrylic acid and (meth)acrylic acid methyl ester, in particular Eudragit® S.
[0122] The inventors have observed that fully neutralized Eudragit® S is capable of forming a film and dissolves readily and completely in water, at least regardless of the pH range found in the intestine (e.g., from about pH 5 to about pH 8). Fully neutralized Eudragit® S is particularly preferred for use as the third polymeric material of the present invention.
[0123] Other polymers suitable for use as the third polymeric material include pharmacologically acceptable non-ionic polymers, i.e., pharmacologically acceptable polymers that do not ionize in aqueous media. In these embodiments, the inner layer further comprises at least one additive selected from a buffer and a base. In particular, the inner layer of these embodiments preferably comprises a base and, optionally, a buffer. In a preferred embodiment, the inner layer comprises both a buffer and a base. Suitable examples of buffers and bases are described below.
[0124] Examples of suitable non-ionic polymers include methylcellulose (MC), hydroxypropylcellulose (HPC), hydroxypropylmethylcellulose (HPMC), poly(ethylene oxide)-grafted polyvinyl alcohol, polyvinylpyrrolidinone (PVP), polyethylene glycol (PEG) and polyvinyl alcohol (PVA). Mixtures of non-ionic polymers may also be used.
[0125] Mixtures of film-forming polymeric materials can be used if desired. The polymeric components in such mixtures can be anionic polymers, nonionic polymers, or mixtures of anionic and nonionic polymers. Examples of suitable mixtures include mixtures of Eudragit® L and Eudragit® S (e.g., 1:1 mixtures) and mixtures of Eudragit® S and HPMC (e.g., 1:1 mixtures). However, the use of certain film-forming polymeric materials alone, such as poly(methacrylic acid / methyl methacrylate) copolymers, especially Eudragit® S, is preferred.
[0126] In a preferred embodiment, the inner layer comprises at least one base. The purpose of the base is to provide an alkaline environment under the outer layer when intestinal fluid begins to penetrate the outer layer. Without being bound by any particular theory, the inventors believe that the alkaline environment promotes the dissolution and thus the disintegration of the outer layer because the pH of the alkaline environment is higher than the pH threshold of the second polymeric material, thereby accelerating the release of the drug from the formulation once the outer coating is dissolved and / or disintegrated.
[0127] In principle, any pharmacologically acceptable base can be used.The base is usually a non-polymeric compound.Suitable bases include inorganic bases such as sodium hydroxide, potassium hydroxide and ammonium hydroxide, and organic bases such as triethanolamine, sodium bicarbonate, potassium carbonate, trisodium phosphate, trisodium citrate or physiologically acceptable amines such as triethylamine.
[0128] The base is preferably selected from the group consisting of a hydroxide base, an alkali metal bicarbonate, an alkali metal carbonate, an alkali metal phosphate, an alkali metal citrate or a physiologically acceptable amine. More preferably, the base is a hydroxide base, particularly preferably sodium hydroxide.
[0129] In embodiments in which the third polymeric material is a fully neutralized polycarboxylic acid polymer, the base entrapped in the inner layer is typically the base used to neutralize the polymer and adjust the pH of the inner layer coating formulation to between about pH 7.5 and about pH 10 (see below).
[0130] In embodiments in which the third polymeric material is a non-ionic polymer, the inner layer typically comprises either a base or, more typically, a combination of a base and a buffer.
[0131] The amount of base present in the inner layer will depend, at least in part, on the final pH of the inner layer coating formulation prior to coating a given batch of cores, the number of cores to be coated in that batch, and the amount of inner layer coating formulation used in the batch coating process.
[0132] The inner layer coating preferably comprises at least one buffering agent. The purpose of the buffering agent is to provide or increase the buffering capacity under the outer layer when intestinal fluid begins to penetrate the outer layer. Without wishing to be bound by a particular theory, the inventors believe that the buffering agent increases the buffering capacity in the dissolving inner layer and aids in the ionization and dissolution of the polymer in the outer layer. At a given pH, the greater the buffering capacity, the faster the dissolution rate of the polymer. In embodiments where a base is present in the inner layer, the buffering agent helps maintain an alkaline environment under the outer layer as intestinal fluid penetrates the outer layer.
[0133] The buffering agent may be an organic acid, for example a pharmacologically acceptable non-polymeric carboxylic acid, for example a carboxylic acid having 1-16, preferably 1-3 carbon atoms. Suitable carboxylic acids are disclosed in WO2008 / 135090A. Citric acid is an example of such a carboxylic acid. The carboxylic acid may be used in the form of a carboxylate, and a mixture of the carboxylic acid, the carboxylate, or both may also be used.
[0134] The buffering agent can also be an inorganic salt, such as an alkali metal salt, an alkaline earth metal salt, an ammonium salt, and a soluble metal salt. The metals of the soluble metal salt include manganese, iron, copper, zinc, and molybdenum. More preferably, the inorganic salt is selected from chloride, fluoride, bromide, iodide, phosphate, nitrate, nitrite, sulfate, and borate. Phosphates, such as potassium dihydrogen phosphate, are preferred over other inorganic buffer salts and organic acid buffers due to their greater buffering capacity at the pH of the coating solution, such as pH 8.
[0135] The buffering agent is typically present in the inner layer in an amount of from about 0.1% to about 60% by weight, for example, from about 0.1% to about 50% by weight, preferably from about 0.1% to about 40% by weight, more preferably from about 0.1% to about 20% by weight, more preferably from about 0.1% to about 4% by weight, more preferably from about 0.1% to about 3% by weight, and most preferably about 1% by weight, based on the dry weight of the third polymeric material.
[0136] In addition to a buffer and / or a base, the inner layer may contain conventional excipients for polymeric films, such as excipients selected from plasticizers (e.g., triethyl citrate), anti-blocking agents (e.g., GMS) and surfactants (e.g., polysorbate 80).
[0137] The thickness of the inner coating on the core is typically about 10 μm to about 150 μm, although the thickness of the particular coating will vary depending on the composition of the coating and the size of the core.
[0138] As with the outer layer, the amount of polymer in the inner layer is independent of the size of the core. The inner layer typically has a polymer content of about 2 mg / cm based on the dry weight of the third polymeric material. 2 More than about 10mg / cm 2 Less than about 2 mg / cm 2 More than 8mg / cm 2 Below 3 mg / cm, most preferably about 2 More than about 7mg / cm 2 For example, about 5 mg / cm 2 The polymer coating is
[0139] Partition layer The formulations of the present invention may have additional (or separator) layers between the active core and the inner and / or outer layer.
[0140] There may be formulations according to the present invention in which the composition of the core is not compatible with the delayed release coating.In such cases, it may be desirable to include a partition layer to separate the core from the coating.For example, the present invention includes an embodiment in which the inner layer provides an alkaline environment that is believed to aid in the dissolution and decomposition of the outer layer.However, if the core contains a drug with an acidic group, the inner layer may not be compatible with the core.An example of a drug with an acidic group is 5-ASA.In such cases, it is usually appropriate to have a partition layer.
[0141] Any suitable barrier layer known to those skilled in the art can be used. In a preferred embodiment, the barrier layer comprises a film-forming non-ionic polymer. Suitable non-ionic polymers include methylcellulose (MC), hydroxypropylcellulose (HPC), hydroxypropylmethylcellulose (HPMC), poly(ethylene oxide)-graft-polyvinyl alcohol, polyvinylpyrrolidone (PVP), polyethylene glycol (PEG) and polyvinyl alcohol (PVA). Non-ionic cellulosic polymers (e.g., HPMC) are preferred, as are PVA. Mixtures of non-ionic polymers can also be used. A particularly preferred mixture is HPMC and PEG. The barrier layer can further include a plasticizer. Suitable plasticizers include, but are not limited to, polyethylene glycol, triethyl citrate, triacetin and acetyltriethyl citrate.
[0142] The formulation may also include an intermediate layer between the outer layer and the inner layer, provided that the intermediate layer does not adversely affect the release characteristics of the formulation. However, the outer layer is usually provided in contact with the inner layer, i.e., the outer layer is usually provided directly on the inner layer, i.e., there is usually no intermediate layer separating the inner and outer layers. EXAMPLES
[0143] Some preferred embodiments of the present invention will now be described with reference to the drawings.
[0144] FIG. 1 is a graph showing the correlation between compression pressure and tablet hardness for 1600 mg 5-ASA tablet cores produced using an external lubricant according to Examples 2A-2G.
[0145] FIG. 2 is a graph showing the correlation between tablet hardness and friability for 1600 mg 5-ASA tablet cores produced using external lubricants according to Examples 2A-2G.
[0146] FIG. 3 is a graph showing the correlation between compression pressure and tablet hardness for 1600 mg 5-ASA tablet cores produced using internal lubricants according to Comparative Examples 3A-3H.
[0147] FIG. 4 is a graph showing the correlation between tablet hardness and friability for 1600 mg 5-ASA tablet cores prepared using internal lubricants according to Comparative Examples 3A-3H.
[0148] FIG. 5 is a graph comparing drug release as a function of time from coated 5-ASA tablets according to Examples 5 and 6 when pre-exposed to 0.1 M HCl for 2 hours followed by exposure to Krebs buffer (pH 7.4) for 10 hours.
[0149] material Eudragit® S100 was purchased from Evonik GmbH (Darmstadt, Germany). Corn starch (Eurylon® 6 and AmyloN-400) was purchased from Roquette (Lestrem, France). Polysorbate 80 (Tween® 80), butan-1-ol, triethyl citrate (TEC), ethanol 96%, potassium dihydrogen phosphate (KH2PO4), sodium hydrogen phosphate dibasic dihydrate (Na2HPO4·2H2O) and sodium hydroxide were all purchased from Sigma-Aldrich (Buchs, Switzerland). Hydroxypropyl methylcellulose (HPMC, Pharmacoat® 603) was purchased from Shin-Etsu. Glyceryl monostearate (GMS) was purchased from Cognis. Red and yellow iron oxides (Sicovit) were purchased from BASF. Microcrystalline cellulose (Avicel® pH 102) was purchased from FMS Biopolymer. Sodium starch glycolate (Explotab®) was purchased from JRS Pharma. Colloidal silicon dioxide (Aerosil® 200) was purchased from Degussa.
[0150] Preparation of tablet cores Example 1: Preparation of 1200 mg 5-ASA Tablet Cores with External Lubrication (Lab Scale) Oval 1200 mg cores were prepared according to the following method: The amounts of each ingredient per tablet core are summarized in Table 1.
[0151] Mesalazine was charged into a high shear mixer granulator and an aqueous composition of hydroxypropyl methylcellulose (Pharmacoat® 603) was added slowly over 2 minutes at a mixing speed of 650 rpm. Mixing was continued for an additional minute at 650 rpm, then the sediment was removed from the walls and top of the mixing vessel and the remaining mixture was mixed for an additional 3 minutes at 650 rpm with a chopper blade at a speed of 600 rpm. The wet granules were passed through an oscillating granulator (2 mm sieve) and then dried in a fluid bed dryer at an inlet air temperature of about 50° C. and a product temperature of 38° C. The dried granules were sieved through the oscillating granulator (1 mm sieve).
[0152] The dried granules were blended with microcrystalline cellulose (Avicel® pH 102) and sodium starch glycolate (Explotab®) in a cube blender for 10 minutes at 20 rpm. Tableting was carried out using a single punch eccentric tablet press. Magnesium stearate was applied with a brush to the punches and dies of the tablet press.
[0153] Comparative Examples 1A-1C: Preparation of 1200 mg 5-ASA Tablet Cores with Internal Lubrication (Lab Scale) Oval 1200 mg cores were prepared according to the following method: The amounts of each ingredient per tablet core are summarized in Table 1.
[0154] [Table 1]
[0155] Mesalazine was charged into a high shear mixer granulator and an aqueous composition of hydroxypropyl methylcellulose (Pharmacoat® 603) was added slowly over 2 minutes at a mixing speed of 650 rpm. Mixing was continued for an additional minute at 650 rpm, then the sediment was removed from the walls and top of the mixing vessel and the remaining mixture was mixed for an additional 3 minutes at 650 rpm with a chopper blade at a speed of 600 rpm. The wet granules were passed through an oscillating granulator (2 mm sieve) and then dried in a fluid bed dryer at an inlet air temperature of about 50° C. and a product temperature of 38° C. The dried granules were sieved through the oscillating granulator (1 mm sieve).
[0156] The dried granules were blended with microcrystalline cellulose (Avicel® pH 102) and sodium starch glycolate (Explotab®) in a cube blender for 10 minutes at 20 rpm. Magnesium stearate was added and the resulting mixture was mixed for 3 minutes. Tableting was carried out using a single punch eccentric tablet press.
[0157] Examples 2A-2G: Preparation of 1600 mg 5-ASA tablet cores with external lubrication (pilot scale) Oval 1600 mg cores were prepared according to the following method: The amounts of each ingredient per tablet core and per batch of 20,000 tablet cores are summarized in Table 2.
[0158] [Table 2]
[0159] Mesalazine (8 kg) and an aqueous solution containing hydroxypropyl methylcellulose (160 g, Pharmacoat® 603) were granulated in a high speed mixer granulator. The wet granules were passed through a 9.4 mm sieve (Comil) and then dried in a fluid bed dryer at an inlet air temperature of about 80° C. until the product temperature reached 42° C. The dried granules were sieved using a 1.6 mm grater sieve. The granulation was repeated for three more 8 kg batches of mesalazine.
[0160] The mixed batch of dry granules was blended with microcrystalline cellulose (Avicel® pH 102) and sodium starch glycolate (Explotab®) in an 80 L drum for approximately 20 minutes at 28 rpm. Magnesium stearate and colloidal silicon dioxide (Aerosil® 200) were both pre-blended separately with approximately 500 g of the compression blend and passed through a 1 mm sieve before being added to the remaining compression blend. The mixture was blended for approximately 5 minutes at 28 rpm to form the final compression blend.
[0161] Compression of the final compression blend was carried out using a Fette P1200 tablet press in combination with an external lubrication system (PKB). Magnesium stearate was sprayed onto the tablet press punches at a rate of 400 g / hr. The tablet press was run at various compression pressures.
[0162] Comparative Examples 3A-3H: Preparation of 1600 mg 5-ASA Tablet Cores with Internal Lubrication (Pilot Scale) Oval 1600 mg cores were prepared according to the following method: The amounts of each ingredient per tablet core and per batch of 20,000 tablet cores are summarized in Table 3.
[0163] [Table 3]
[0164] Mesalazine (8 kg) and an aqueous solution of hydroxypropyl methylcellulose (160 g, Pharmacoat® 603) were granulated in a high shear mixer granulator. The wet granules were passed through a 9.4 mm sieve (Comil) and then dried in a fluid bed dryer at an inlet air temperature of about 80° C. until the product temperature reached 42° C. The dried granules were sieved using a 1.6 mm grater sieve. The granulation was repeated for three more 8 kg batches of mesalazine.
[0165] The mixed batch of dry granules was blended with microcrystalline cellulose (Avicel® pH 102) and sodium starch glycolate (Explotab®) in an 80 L drum for approximately 20 minutes at 28 rpm. Magnesium stearate and colloidal silicon dioxide (Aerosil® 200) were both pre-blended separately with approximately 500 g of the mixture of mesalazine granules, microcrystalline cellulose and sodium starch glycolate, passed through a 1 mm sieve and then added to the remainder of the mixture. The mixture was blended for approximately 5 minutes at 28 rpm to form the final compression blend.
[0166] Compression of the final compression blend was carried out using a Fette P1200 tablet press at a compression speed of 20,000 tablets / hour. The tablet press was operated at various compression pressures ranging from 27 to 40 kN.
[0167] Examples 3 and 4: Scale-up of the process to manufacture 1600 mg 5-ASA tablet cores using external lubrication Oval 1600 mg cores were prepared according to the following method: The amounts of each ingredient per tablet core are summarized in Table 4.
[0168] [Table 4]
[0169] Mesalazine (8 kg) and an aqueous solution of hydroxypropyl methylcellulose (160 g, Pharmacoat® 603) were granulated in a high shear mixer granulator. The wet granules were passed through a 9.4 mm sieve (Comil) and then dried in a fluid bed dryer for about 45 minutes at an inlet air temperature of 80° C. and a product temperature of about 42° C. The dried granules were sieved using a 1.6 mm grater (Comil). Depending on the total batch size, multiple granulation batches were performed and mixed to perform the final blend.
[0170] The mixed batch of dry granules was blended with microcrystalline cellulose (Avicel® pH 102) and sodium starch glycolate (Explotab®) in an 80 L bin blender at 28 rpm. Magnesium stearate and colloidal silicon dioxide (Aerosil® 200) were both pre-blended separately with approximately 500 g of the mixture of mesalazine granules, microcrystalline cellulose and sodium starch glycolate, passed through a 1 mm sieve and then added to the remainder of the mixture. The mixture was blended at 28 rpm for approximately 5 minutes to form the final compression blend.
[0171] Various properties were measured on the granules and compressed blends, as summarized in Table 5 below.
[0172] [Table 5]
[0173] Compression of the final compression blend was carried out using a Fette P1200 tablet press coupled with an external lubrication system (PKB) at a compression speed of 20,000 tablets / hour. Magnesium stearate was sprayed onto the punches and dies of the tablet press at a dosage of 400 g / hour.
[0174] Drug Release Test #1: Dissolution in 0.05M Phosphate Buffer at pH 7.2 In vitro dissolution tests were performed with a USP type II apparatus using 0.05 M phosphate buffer at pH 7.2. A paddle rotation speed of 50 rpm was used during dissolution (30 min) and then a rotation speed of 100 rpm was used for an additional 30 min to ensure recovery of the drug content in the dosage form.
[0175] result The physical properties of the 1200 mg tablet cores produced in Example 1 and Comparative Examples 1A-1C are summarized in Table 6 below. The tablet cores according to Example 1 exhibit superior hardness and friability when compared to Comparative Examples 1A-1C. This data shows that when produced on a laboratory scale, the use of an external lubricant produces tablet cores with superior physical properties than those produced using only an internal lubricant.
[0176] [Table 6]
[0177] The drug release profiles of tablet cores of Example 1 and Comparative Examples 1A-1C after exposure to 0.05M phosphate buffer (Drug Release Test #1) are also summarized in Table 6. The data clearly show that tablet cores according to the present invention manufactured using an external lubricant (Example 1) have significantly shorter disintegration times and faster dissolution rates when compared to those prepared using an internal lubricant (Comparative Examples 1A-1C).
[0178] Pilot plant scale production of 1600 mg tablet cores using external lubrication was also possible over a wide range of compression pressures (Table 7). The small variation in tablet mass with increasing compression pressure indicates that the compression blends have acceptable flow characteristics. No capping was observed for any of the tablets tested. A significant reduction in ejection pressure is observed when both the die and punches of the tablet press are lubricated (Example 2G).
[0179] [Table 7]
[0180] A correlation is seen between increasing compression force and tablet hardness (Figure 1), as well as a correlation between tablet hardness and friability (Figure 2).
[0181] In comparison, tablet cores compressed using only internal lubricant tend to cap during friability testing (Table 8, Comparative Examples 3B and 3D-3F). Tablet sticking to the punches of the tablet press was also observed, with high values of ejection pressure indicating insufficient levels of lubricant in the compression blend (Table 8). However, as shown in Comparative Examples 1A-1B, further increases in the amount of internal lubricant have a detrimental effect on tablet quality.
[0182] [Table 8]
[0183] Furthermore, using internal lubrication alone, compression of the compression blend is only possible over a narrow range of compression pressures, and no correlation is observed between compression pressure and hardness, or between hardness and friability (see Figures 3 and 4). Since an increase in compression pressure does not result in an increase in tablet hardness, it appears that the presence of lubricant in the compression blend (internal lubrication) may hinder compression of the blend.
[0184] Scaling up of the external lubrication process to prepare 1600 mg tablet cores was successful, providing tablet cores with acceptable strength, represented by low friability and high hardness (Table 9). The tablet cores according to the present invention also exhibit rapid disintegration times.
[0185] [Table 9]
[0186] Preparation of coated tablet cores Examples 5 and 6: Coating of 1200 mg and 1600 mg 5-ASA tablet cores Tablet cores containing 1200 mg and 1600 mg mesalazine (5-ASA) were prepared.
[0187] 3 mg / cm 2 of hypromellose (hydroxypropyl methylcellulose, HPMC) and 20% Macrogol 6000, with a partition layer of 5 mg / cm of 70% methacrylic acid-methyl methacrylate copolymer (ratio 1:2 (Eudragit® S100)) and 30% high amylose starch. 2 The tablet cores of Example 5 (1200 mg of 5-ASA) were coated with an outer layer of
[0188] The same partition layer as in Example 5 and 5 mg / cm of methacrylic acid-methyl methacrylate copolymer (ratio 1:2 (Eudragit® S100)) and 1% potassium dihydrogen phosphate neutralized to pH 8. 2 and an inner layer of 5 mg / cm of methacrylic acid-methyl methacrylate copolymer (ratio 1:2 (Eudragit® S100)). 2 The tablet cores of Example 6 (1600 mg 5-ASA) were coated with an outer layer of
[0189] Partition layer The barrier layer was formed by spray coating in the following amounts:
[0190] [Table 10]
[0191] HPMC coating amount is 3mg / cm 2 The partition layer coating preparation was sprayed onto the tablet cores using a pan coater until a coating density of 100% was reached to produce intermediate (partition layer) coated cores.
[0192] The spray coating parameters were as follows:
[0193] [Table 11]
[0194] Inner layer (of Example 6) The partition-coated tablet cores were then coated with an inner layer coating of partially neutralized methacrylic acid-methyl methacrylate copolymer (ratio 1:2; Eudragit® S100) and 1% KH2PO4 buffer.
[0195] The inner layer was formed by spray coating in the following amounts:
[0196] [Table 12]
[0197] The pH was adjusted using 1M NaOH until pH 8. KH2PO4 was dissolved in distilled water and then partially neutralized Eudragit® S100 was dispersed.
[0198] Coating amount of Eudragit® S100: 5mg / cm 2 The inner layer coating formulation was sprayed onto the partition layer coated cores using a pan coater until a coating viscosity of 100 μm was reached to produce intermediate (inner layer) coated cores.
[0199] The spray coating parameters were as follows:
[0200] [Table 13]
[0201] Outer layer (of Example 5) The partition-coated tablet cores were coated with an outer coating formed of 70% methacrylic acid-methyl methacrylate copolymer (1:2; Eudragit® S100) and 30% high amylose starch.
[0202] The outer coating was formed from a mixture of an aqueous starch dispersion and Eudragit® S100 in ethanol in the following amounts:
[0203] [Table 14]
[0204] An aqueous starch dispersion was prepared by dispersing high amylose maize starch (Eurylon® 6) in butan-1-ol and then in water under magnetic stirring. The ratio of maize starch:butan-1-ol:water was 1:1:12.5. The resulting dispersion was heated to boiling and then cooled with stirring overnight.
[0205] A Eudragit® S100 solution was prepared by dispersing Eudragit® S100 in 96% ethanol under high speed stirring, the final solution contained approximately 6% polymer solids.
[0206] Under stirring, the starch dispersion was added dropwise to the Eudragit® S100 solution to give a 70:30 ratio of Eudragit® S100:starch. The mixture was stirred for 1 hour, 40% TEC (based on the polymer weight of Eudragit® S100) and 10% GMS (based on the polymer weight of Eudragit® S100) were added and mixed for an additional 30 minutes. A suspension of 13.16% red iron oxide (based on the polymer weight of Eudragit® S100) and 2.23% yellow iron oxide (based on the polymer weight of Eudragit® S100) was added and the mixture was stirred for an additional 10 minutes.
[0207] GMS was added in the form of an emulsion prepared at a concentration of 5% w / w. Polysorbate 80 (Tween, 40% based on GMS weight) was dissolved in distilled water and then GMS was dispersed. The dispersion was heated at 75° C. for 15 minutes under strong magnetic stirring to form an emulsion. The emulsion was cooled at room temperature while stirring.
[0208] A pigment suspension was formed by suspending red and yellow iron oxide pigments in 96% ethanol for 10 minutes under homogenization.
[0209] Coating amount of Eudragit® S100: 5mg / cm 2 The final outer coating formulation was sprayed onto the partition layer coated tablet cores until a coating viscosity of 100% was reached.
[0210] Outer layer (Example 6) The partition and inner coated tablet cores were coated with an outer coating formed from methacrylic acid-methyl methacrylate copolymer (1:2; Eudragit® S100).
[0211] The outer coating was formed from a solution of Eudragit® S100 in ethanol in the following amounts:
[0212] [Table 15]
[0213] The outer coating was prepared by dispersing Eudragit® S100 in 96% ethanol under high speed stirring, then adding the TEC and GMS emulsions (prepared as in Example 5). Finally, the suspensions of red and yellow iron oxides (prepared as in Example 5) were added to the mixture, and the mixture was stirred for an additional 10 minutes.
[0214] Coating amount of Eudragit® S100: 5mg / cm 2 The final outer coating formulation was sprayed onto the partition and inner layer coated tablet cores until a coating viscosity of 100% was reached.
[0215] The spray coating parameters for the formation of the outer layer coating were as follows:
[0216] [Table 16]
[0217] Drug Release Test #2: Simulated fasting conditions and then dissolved in Hanks buffer at pH 6.8 In vitro dissolution testing was performed with a USP Type II apparatus using a paddle speed of 50 rpm and a medium temperature of 37° C.±0.5° C. To simulate the “fasted” condition, tablets were first tested in 0.1 M HCl for 2 hours and then in Hank's buffer (pH 6.8) for 10 hours.
[0218] The pH of the buffer was stabilized at 6.8 ± 0.05 by continuous sparging with 5% CO2 / 95% O2. Absorbance measurements were performed at 5 min intervals, with absorbance wavelengths of 301 nm in HCl and 330 nm in Hank's buffer pH 6.8.
[0219] Drug Release Test #3: Simulated fasting and then dissolved in Krebs buffer at pH 7.4 In vitro dissolution testing was performed with a USP Type II apparatus using a paddle speed of 50 rpm and a medium temperature of 37°C ± 0.5°C.
[0220] To mimic the "fasted" state, tablets were first tested in 0.1 M HCl for 2 hours and then in Krebs buffer (pH 7.4) for 10 hours.
[0221] result The 1200 mg and 1600 mg tablet cores of the present invention could be coated with known delayed release coatings. The results demonstrate that the coated tablets prepared according to the present invention are resistant to simulated gastric fluids and exhibit rapid drug release upon exposure to simulated conditions of the ileocolonic region.
[0222] The 1200 mg coated tablet of Example 5 and the 1600 mg coated tablet of Example 6 were tested in vitro for drug release in pH 6.8 Hanks buffer after exposure to simulated gastric conditions. In both cases, the coated tablets were resistant to the stomach, with less than 5% drug release when exposed to simulated proximal small intestine conditions (pH 6.8 Hanks buffer). This indicates the robustness of the coated tablets when passing through the small intestine.
[0223] However, it should be noted that when exposed to pH 7.4 to mimic conditions in the ileocolonic region (Drug Release Study #3), rapid drug release was observed for both the 1200 mg and 1600 mg coated tablets of the present invention (Figure 5).
[0224] It will be understood that the invention is not limited to the details set forth above with respect to the preferred embodiments, but that numerous modifications and variations can be made without departing from the scope of the invention as defined by the following claims.
Claims
1. 1. A coatable core for a modified release formulation for oral administration comprising: The coatable core has a friability of 0% to less than 0.5%, a hardness of 200N to 330N, and a high drug load of at least 70% by weight based on the total weight of the coatable core, and comprises the following components: Amounts of drug greater than 1200 mg; a pharmacy acceptable lubricant in an amount greater than 0% by weight and less than or equal to 0.25% by weight, based on the total weight of the coatable core; and A pharmacologically acceptable disintegrant in an amount of 0.5% to 5% by weight based on the total weight of the coatable core. comprising The coatable core, wherein the disintegrant is selected from croscarmellose sodium, cross-linked polyvinylpyrrolidone, cross-linked alginic acid, calcium silicate and sodium starch glycolate.
2. A coatable core as described in claim 1 having a wear rate of 0.1% or more and 0.25% or less.
3. A coatable core as described in claim 1 having a wear rate of 0.1% or more and 0.2% or less.
4. A coatable core according to any one of claims 1 to 3, having a disintegration time of less than 10 minutes.
5. A coatable core according to any one of claims 1 to 3, having a disintegration time of less than 5 minutes.
6. The coatable core of any one of claims 1 to 5, having a drug amount of 85% to 95% by weight, based on the total weight of the coatable core.
7. The coatable core according to any one of claims 1 to 6, wherein the disintegrant is present in an amount of from 0.5% to 3% by weight, based on the total weight of the coatable core.
8. A coatable core according to any one of claims 1 to 7, wherein the lubricant is present in an amount of 0.1% by weight or less, based on the total weight of the coatable core.
9. A coatable core according to any one of claims 1 to 7, wherein the lubricant is present in an amount of 0.05% by weight or less, based on the total weight of the coatable core.
10. 10. The coatable core of any one of claims 1 to 9, wherein the drug is present in the coatable core in an amount of from 1250 mg to 1650 mg, or from 1450 mg to 1650 mg, or from 1550 mg to 1650 mg, or 1600 mg.
11. The coatable core according to any one of claims 1 to 10, wherein the coatable core is a tablet.
12. A coatable core according to any one of claims 1 to 11, wherein the coatable core comprises one or more additional pharmacologically acceptable excipients.
13. 1. A delayed release formulation for oral administration for delivering a drug to the intestine of a subject, comprising: The delayed release formulation comprises a core and a coating for the core, The core has a friability of 0% to less than 0.5%, a hardness of 200N to 330N, and a high drug content of at least 70% by weight based on the total weight of the coatable core, and comprises the following components: Amounts of drug greater than 1200 mg; a pharmacy acceptable lubricant in an amount greater than 0% by weight and not greater than 0.25% by weight, based on the total weight of the coatable core; and A pharmacologically acceptable disintegrant in an amount of 0.5% to 5% by weight based on the total weight of the coatable core. comprising The disintegrant is selected from croscarmellose sodium, cross-linked polyvinylpyrrolidone, cross-linked alginic acid, calcium silicate and sodium starch glycolate; the coating comprises an outer layer and, optionally, at least one layer located between the core and the outer layer selected from the group consisting of a barrier layer and an inner layer; The outer layer comprises a film-forming enteric polymer having a pH threshold of 5 or more, and optionally an enzymatically degradable polymer that is degraded by colonic enzymes; the inner layer comprises a polymeric material that is soluble in intestinal or gastrointestinal fluids; the polymeric material is selected from the group consisting of at least partially neutralized polycarboxylic acid polymers and non-ionic polymers, with the proviso that when the polymeric material is a non-ionic polymer, the inner layer comprises at least one additive selected from a buffer and a base; The delayed release formulation, wherein the barrier layer comprises a non-ionic polymer that is soluble in intestinal or gastrointestinal fluids.
14. 14. The delayed release formulation of claim 13, wherein the outer layer comprises an enzymatically degradable polymer that is degraded by colonic enzymes.
15. the outer layer comprises a film-forming enteric polymer having a pH threshold of 5 or more and an enzymatically degradable polymer that is degraded by colonic enzymes; 15. The delayed release formulation of claim 14, wherein the outer layer is formed on the core using a coating preparation formed by mixing the enzymatically degradable polymer in an aqueous medium with the film-forming enteric polymer in an organic medium.
16. The delayed release formulation according to any one of claims 13 to 15, wherein the coatable core has a friability of 0.1% to 0.25%.
17. The delayed release formulation of any one of claims 13 to 15, wherein the coatable core has a friability of 0.1% or more and 0.2% or less.
18. The delayed release formulation according to any one of claims 13 to 17, wherein the coatable core has a disintegration time of less than 10 minutes.
19. The delayed release formulation of any one of claims 13 to 17, wherein the coatable core has a disintegration time of less than 5 minutes.
20. The delayed release formulation according to any one of claims 13 to 19, wherein the coatable core has a drug amount of 85% to 95% by weight, based on the total weight of the coatable core.
21. The delayed release formulation according to any one of claims 13 to 20, wherein the disintegrant is present in an amount of 0.5% to 3% by weight, based on the total weight of the coatable core.
22. The delayed release formulation according to any one of claims 13 to 21, wherein the lubricant is present in an amount of 0.1% by weight or less.
23. The delayed release formulation of any one of claims 13 to 21, wherein the lubricant is present in an amount of 0.05% by weight or less.
24. 24. The delayed release formulation of any one of claims 13 to 23, wherein the drug is present in the core in an amount of from 1250 mg to 1650 mg, or from 1450 mg to 1650 mg, or from 1550 mg to 1650 mg, or 1600 mg.
25. The delayed release formulation according to any one of claims 13 to 24, wherein the coatable core is a tablet.
26. The delayed release formulation of any one of claims 13 to 25, wherein the coatable core comprises one or more additional pharmacologically acceptable excipients.